Capturing Change: Creating a Template to Examine the Educational Experiences and Outcomes of the AONE Foundation Nurse Manager Fellowship. (March 2017) - Mackoff, Barbara L.; Meadows, Mary T.; Nash, Alice
Abstract : OBJECTIVE: The aim of the study is to create a mixed-methods evaluation template to examine the educational experiences and outcomes of participants in the Nurse Manager Fellowship (NMF) sponsored by the American Organization of Nurse Executives (AONE) Foundation. The focus was to capture change as reported by the nurse manager (NM) fellows and the senior leaders who sponsored them and to gain access to the participants' lived experiences as leadership learners. BACKGROUND: The AONE Foundation's NMF conducts a yearlong professional development program with a cohort of 30 fellows who meet 4 times a year in face-to-face sessions and complete a capstone project. METHODS: Four data collection methods were used. Participants completed 2 quantitative leadership program outcome surveys, as well as 1 qualitative measure to focus on self-perceived change outcomes. Their sponsors completed a qualitative perception of change measure. RESULTS: The participants' reflections, self-reports, and the sponsor observations capture impactful changes in the NM fellows' increases in knowledge and application in the spheres of self, organization, and community. The enhancement of the participants' self-identification as leaders was also demonstrated. CONCLUSIONS: The variety of data collection methods suggests both distinct choices in creating future evaluation templates for the fellowship and approaches that might be adapted by other organizations.